Edukasi Pengelolaan Dan Pemilahan Sampah Organik Dan Anorganik Di Desa Pecalongan Bondowoso - Yuwana, Siti Indah Purwaning; Adlan, Mohammad Fuad Alfin Sayuti (FORDICATE, 2021)
Garbage is a serious problem that is often faced by the populationtoday. This Community Service activity was carried out in Pecalongan Village,Sukosari, Bondowoso Regency. Community knowledge in Pecalongan Villageabout waste and its management is still minimal. Inadequate supporting facilitiesalso exacerbate this condition. Therefore, it is important to raise public awarenessso that they do not just throw garbage and educate them on how to sort waste.Starting from these problems, this community service activity aims to providesolutions through education on the importance of maintaining cleanliness,selecting and distinguishing organic and inorganic waste and utilizing processedwaste so that it has economic value. The tangible form of this activity is in the formof assistance in providing facilities for segregated waste bins. The method used inthe implementation of this service activity is education through the stages ofsocialization, licensing, preparation, implementation and evaluation. As a result ofthis community service activity, community members become concerned about theimportance of maintaining cleanliness, an increased understanding of wastesorting independently and knowledge of its benefits. In addition, the people ofPecalongan can also find out the benefits of processing waste using the 3Rmethod, namely: Reduce, Reuse, Recycle.